Developing a Psychological Assessment Tool Using LinkedIn Profile Pictures for IT Leadership Recruitment - Ansab, Khalid (2024)
This study explores the use of LinkedIn profile pictures as a tool to assess leadership potential in the IT industry. The novel leadership assessment was developed through phenomenological interviews with experienced and senior IT executives. The interviews aimed to identify visual cues associated with leadership qualities. These qualitative insights were analysed through thematic analysis, leading to the generation of assessment items. The scale was administered on IT professionals (N=400). Exploratory Factor Analysis revealed the factor structure and three distinct factors: Professional Composition and Context (PCC), High Quality and Presentation (HQP), and Professional Intent and Neutrality (PIN). These factors demonstrated significant moderate correlations (p < .01) and moderate to good internal consistency (PCC: α = .72, HQP: α = .70, PIN: α = .63). Further validation through case studies demonstrated the scale’s effectiveness in real-world scenarios, confirming its practical utility. The findings suggest that this leadership assessment scale provides a robust tool for assessing leadership potential via LinkedIn profile pictures. This scale can be utilised in recruitment, leadership development, and training within the IT industry. On the contrary, the limitation of the scale restricts its generalisability and standardised interpretation. The study recruited a demographically homogenous sample from Business Process Outsourcing sector within the IT industry which limits the generalisability to other sectors or industries. Moreover, absence of a structured interpretation manual and established cut-off scores restricts standardised interpretation of the leadership potential among the raters. To address these limitations, future studies can increase the sample size and diversity, develop a structured interpretation manual, establish cut-off scores, and explore other methods, such as Confirmatory Factor Analysis, to further validate the scale and improve its applicability across different sectors and industries. In accordance with ethical considerations, the research adhered to the guidelines outlined by the American Psychological Association, ensuring the well-being and rights of the participants, including informed consent, confidentiality, and privacy. By upholding these ethical standards. The study offers a new approach to integrating visual analysis into Industrial/Organisational psychology. By leveraging LinkedIn profile pictures as a tool for assessing leadership potential, this research paves the way for utilizing visual cues in psychological assessments. This approach aligns with the demands of the tech-driven era, offering a modern solution that bridges psychological assessment with technology, meeting the evolving needs of contemporary organizations.